The role of boron on grain refinement in sterling silver alloy - Sirisiwan Sakultanchareonchai (2018)
The role of boron on grain refinement in the Sterling silver alloys grade 950 containing 3.9%Cu, 0.08%Si, 0.11%Sn and 1%Zn without and with boron addition was studied. Microstructure of the silver alloys was investigated by light microscopy, electron probe microanalysis, scanning and transmission electron microscopy. To study microstructural phenomena at grain boundaries, thin foils for transmission electron microscopy were prepared by focused ion beam method, cross-sectional along the grain boundaries. The results revealed that addition of boron at less than 10 ppm level into the alloy reduced the grain size by a factor of about three. Nano-scale copper-rich particles were found at grain boundary vicinity in the silver alloy with boron addition. Enhancement of segregation ability of copper and a possibility of co-segregation of boron and carbon with copper to grain boundaries leading to precipitation of fine particles were therefore proposed. This supports the constitutionally-undercooled-zone mechanism of grain refinement.